2008
DOI: 10.1007/s10201-008-0249-1
|View full text |Cite
|
Sign up to set email alerts
|

Uranium sorption onto natural sediments within a small stream in central Japan

Abstract: In this study, we surveyed the uranium (U) load in stream water within a humid forest in Japan, and clarified the fact that changes in U load depended on the amount of sediment accumulated behind dams constructed along the stream. To elucidate the relationship between U and the accumulated sediments, we conducted U sorption experiments in the laboratory using stream water and sampled sediments. The chemistry of the stream water was analyzed in the field for pH, electrical conductivity (EC), and temperature, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In the presence of high carbonate, UO 2 2+ forms even more favorable CaUO 2 (CO 3 ) 3 2– , Ca 2 UO 2 (CO 3 ) 3(aq) , and MgUO 2 (CO 3 ) 3 2– species . The mobilized U is also known to adsorb to minerals (e.g., Fe oxides, MnO 2 , calcite, , clay , ) and organic matter. , U can also reprecipitate to form secondary minerals depending upon the availability of constituent co-ions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of high carbonate, UO 2 2+ forms even more favorable CaUO 2 (CO 3 ) 3 2– , Ca 2 UO 2 (CO 3 ) 3(aq) , and MgUO 2 (CO 3 ) 3 2– species . The mobilized U is also known to adsorb to minerals (e.g., Fe oxides, MnO 2 , calcite, , clay , ) and organic matter. , U can also reprecipitate to form secondary minerals depending upon the availability of constituent co-ions …”
Section: Introductionmentioning
confidence: 99%
“…30 The mobilized U is also known to adsorb to minerals (e.g., Fe oxides, 31−33 MnO 2 , 34 calcite, 35,36 clay 37,38 ) and organic matter. 39,40 U can also reprecipitate to form secondary minerals depending upon the availability of constituent coions. 41 Co-occurrences of elevated fluoride and uranium levels in groundwater have been identified in many parts of India and also in Myanmar.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A similar case has been reviewed and reported by Shamim Akhtar [43], showing that U deposits in Pakistan were formed in a reduced environment. Various studies have reported that U solubility is affected by its speciation and aqueous chemistry including organic matter (OM) concentrations [44][45][46]. Low OM concentration was shown to promote U solubility, whereas high OM concentration may immobilize U [47].…”
Section: Mineral Association and Geochemical Characteristicsmentioning
confidence: 99%
“…Various studies have reported that U solubility is affected by its speciation and aqueous chemistry including organic matter (OM) concentrations [44][45][46]. Low OM concentration was shown to promote U solubility, whereas high OM concentration may immobilize U [47].…”
Section: Mineral Association and Geochemical Characteristicsmentioning
confidence: 99%
“…Uranium is known for its toxicity, apart from the fact that ingestion of uranium can damage the liver and cause acute renal failure in humans [ 1 ]. The uranyl ion (UO₂⁺) occurs in oxidation state 6+ and is the most stable form of uranium in aqueous solution [ 2 , 3 , 4 ]. According to safety regulations, uranium consumption in drinking water should be less than 0.015 mg/L [ 5 ].…”
Section: Introductionmentioning
confidence: 99%